Community Policing sebagai Bentuk Pengendalian Sosial - Monica Margaret (Universitas Budi Luhur, 2020)
The Culture of Control aims to describe crime control and cultural practices that give rise to crime. The anchor oif this foirm of soicial conitrol is an institution that handles crime, danger, delinquency ani otheri sociail problems, includiing the criminal jusitice sysitem, health syistem, immigraition and border controls, social welifare systems and urban planniing authoritiies. Controlling crime is one of the main responsibilities of the police. More specifically, fighting crime in society. In other words, the community hopes for a police figure who is suitable or in accordance with his community. This also leads to the griowth of various demands and expectations of thie community towards poilice performance. The poliice anid the commuinity are two strong ministers. Because the police came from the community. While on tihe otiher hanid, the community is needed by the police because it is indeed where the work is done. For all intents and purposes, communitiiy policing in the 1990s reiplaced priofessional police in 1960 as a crime control paradigm. As an idieology and phiilosophy, commiunity policiing is puitting peopie in control of their own environment. Commiunity policiing isi a paradigm based on the assumiption that a collaborative approach betwieen the poliice and the coimmunity wiill faciilitate an informal social control mechanism to mainage risik iand preivent crime. Therefore, crime control is thei responsiibility of a numiber oi sociial actoirsi as citiziens aire enicouraged to be involved in facilitating targieteid actions witih the poilice by idientifiyinig areas where colleictive risk is considered high and by facilitating crime control practices.